simplify cosec(delta)[cos (delta) -1] by expressing it in

terms of (tan (delta/2))

### 1 Answer | Add Yours

`cos(delta)=1-2sin^2(delta/2)`

`cosec(delta)=1/sin(delta)=1/(2sin(delta/2)cos(delta/2))`

Thus

`cosec(delta){cos(delta)-1}=(1/(2sin(delta/2)cos(delta/2)))(-2sin^2(delta/2))`

`` cancel out the terms common in numerator and denominator

=`(-sin(delta/2))/cos(delta/2)`

`=-tan(delta/2)`

Ans.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes